The limit theorems for the sums of random variables related to a Markov chains. II - Statulevičius, V. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:В. А. Статулявичус. Предельные теоремы для сумм случайных величин связанных в цепь Маркова. IIV. Statulevičius. Ribinės teoremos atsitiktinių dydžių, surištų į Markovo grandinę sumoms. II